Corresponding Author Reconfigurable Intelligent Surfaces (RIS) for Energy-Efficient 6G Networks: Design, Optimization, and Applications - Hou, Zhengbing (Transactions on Computer Science and Intelligent Systems Research, 2025)
Reconfigurable intelligent surface (RIS) is introduced as a new technology promising to revolutionize the wireless communication networks, especially for the next generation (6G), due to the fact that RIS can dynamically regulate electromagnetic waves propagation, potentially leading to vast performance improvement and energy-saving. This paper explores the capability of RIS to enhance communication systems in terms of their energy efficiency and signal quality. By incorporating passive, active, and hybrid RIS architectures, the work analyzes their effect on energy efficiency and network throughput. The experimental tests and simulations demonstrate that RIS can offer significant performance gains by mitigating the reliance on legacy high-power base stations and providing improved coverage, especially in critical areas, including urban and complex indoor environments. Moreover, RIS serves to mitigate the scalability issue and cut down the deployment cost, rendering it applicable in the future wireless networks. It also discusses essential engineering problems such as hardware restrictions, synchronization and real-time control. In the future, we expect that metasurfaces, full-duplex RIS, and advanced optimization algorithms powered by AI motivation would be developed to further extend the capabilities of RIS. In conclusion, RIS is a promising technology to shape the future development of 6G networks, enabling more efficient and reliable communication systems.
Keywords: Reconfigurable Intelligent Surfaces, Energy Efficiency, 6G Networks, Hybrid RIS, Smart Cities.